A method for incorporating heterogeneity in measuring the economic carrying capacity of urban infrastructures. (15th January 2022) - Cui, Xinxin; Du, Qiang; Zou, Patrick X.W.; Lu, Cheng; Li, Yaxian
Abstract: The economic carrying capacity of urban infrastructures (UIECC) refers to the ability that the urban infrastructures should have in order to achieve the goal of sustainable development of the urban economy. The UIECC is a crucial factor in the sustainable development of a city. Insufficient UIECC would cause many social problems. Different cities may have many differences in infrastructure construction, economic development and policy support, which lead to heterogeneity among them. If different cities are evaluated under a unified economic standard and criteria, the measurement results would be inaccurate. Therefore, the urban heterogeneity should be considered when calculating UIECC. Through review of literature, which includes indicator selection criteria and policy guidelines, this study establishes an indicator system of UIECC from the joint perspectives of carrier and load. Then, we developed a new UIECC evaluation method that considers heterogeneity, by combining the entropy weight method, the linear weighted sum method and the meta-frontier slack based measurement model. The meta-frontier slack based measurement model considers the slack variables and divides cities into different groups according to the heterogeneity between the cities, which makes the measurement results more accurate and more realistic. Following that, a study of the Beijing-Tianjin-Hebei region was conducted using data covering a period of 14 years (2004–2017) to demonstrate the application of the UIECC model. The results show that: 1) the model developed is applicable and effective for evaluating the UIECC; 2) the existence of heterogeneity hinders the coordinated development of cities; 3) the UIECC potential varies significantly between cities. Based on the results, the following suggestions are proposed: 1) It is important to take heterogeneous measures into consideration to improve the UIECC in the future according to development plans among cities; 2) It is necessary to remove the restrictions on infrastructure imposed by the administrative division between cities; 3) when planning infrastructure development, one should adapt a combined perspective of regional development and economic structure optimization. Highlights: This research proposes a UIECC evaluation method that considers heterogeneity among cities. The UIECC model can measure the potential of economic carrying capacity of urban infrastructures. The causes of UIECC differences are explored to improve UIECC from the perspective of economic structure optimization. It is found that UIECC can improve by economic structure optimization.